Brands matter: Major findings from the Alcohol Brand Research Among Underage Drinkers (ABRAND) project - Roberts, Sarah P. (Addict Res Theory, 2015)
BACKGROUND: Alcohol research focused on underage drinkers has not comprehensively assessed the landscape of brand-level drinking behaviors among youth. This information is needed to profile youth alcohol use accurately, explore its antecedents, and develop appropriate interventions. METHODS: We collected national data on the alcohol brand-level consumption of underage drinkers in the United States and then examined the association between those preferences and several factors including youth exposure to brand-specific alcohol advertising, corporate sponsorships, popular music lyrics, and social networking sites, and alcohol pricing. This paper summarizes our findings, plus the results of other published studies on alcohol branding and youth drinking. RESULTS: Our findings revealed several interesting facts regarding youth drinking. For example, we found that: 1) youth are not drinking the cheapest alcohol brands; 2) youth brand preferences differ from those of adult drinkers; 3) underage drinkers are not opportunistic in their alcohol consumption, but instead consume a very specific set of brands; 4) the brands that youth are heavily exposed to in magazines and television advertising correspond to the brands they most often report consuming; and 5) youth consume more of the alcohol brands to whose advertising they are most heavily exposed. CONCLUSION: The findings presented here suggests that brand-level alcohol research will provide important insight into youth drinking behaviors, the factors that contribute to youth alcohol consumption, and potential avenues for effective public health surveillance and programming.